Revisiting PPP Models for Climate Resilience and Disaster Risk Reduction in Indian Local Bodies: Challenges, Opportunities, and Financial Perspectives - Madapala, Jeevan; Ganesh, M P Suri (International Journal of Engineering and Management Research, 2025)
Natural hazards and climate change are frequently disrupting the communities. These effects are further amplified due to anthropogenic causes and unsustainable development. More often than not, due to limited capabilities, local government is the first victim of such disruptions. In this context, Public-private partnerships (PPP) models present a unique opportunity and overcome limited government funding limitations. This study attempts to explore the potential of PPP models in supporting and financing Climate Change Adaptation (CCA) and Disaster Risk Reduction (DRR) initiatives at the local-body levels. This study reviews both the international case studies from Jamaica, Japan and Latin America and national case studies from Delhi, India’s Smart City Mission. The study identifies the gaps in existing PPP frameworks and emphasises the need for innovative funding methods. The paper also discusses the importance of community engagement, multi-stakeholder engagement and traditional knowledge. Recommendations include enhancing financial resilience through blended finance, resilience bonds, and risk-sharing mechanisms. The paper proposes locally tailored PPP frameworks that prioritise long-term sustainability, capacity building, and responsive financing to foster climate-adaptive infrastructure.